Relación entre el uso excesivo de dispositivos digitales sociales y los niveles de atención en jóvenes - Meléndez Valencia, Angie Nicole (2025)
This research intends to set up the connection between excessive use of social digital devices and levels of attention among second-year high school students at "San Vicente de Paúl," an institution found in Riobamba. The study stems from concerns about the impact that excessive use and prolonged exposure to digital platforms may have on young people's cognitive performance, particularly their ability to maintain attention— understood as the cognitive process that allows individuals to focus their mental resources on a specific stimulus or task.—while concentration refers to the capacity to sustain that attention over a determined period during academic activities. Methodologically, the research follows a quantitative approach, with a non-experimental design and a correlational scope. According to its aim, it is a basic study; according to its setting, it is a field study; and according to its temporal nature, it is cross-sectional. The study population included students from the Educational Unit "San Vicente de Paúl," with a sample of second-year high school students in class "A." A structured survey was used to prove the level of access to social digital devices, and the psychometric D2 Test was employed to assess attention. The results show that a significant percentage of students present medium and low levels of attention, which coincides with daily use of digital devices exceeding four hours. Likewise, a decrease in attentional capacity associated with prolonged and nighttime use of these devices was observed. This study highlights the need to promote a balanced use of technology and to implement psychopedagogical strategies that strengthen attention skills within school contexts.